Investigating the impact of land use land cover change on groundwater level dynamics in the Koraiyar watershed, Coimbatore District, Tamil Nadu, India - Naik, S. R. Sreerama; Masilamani, P.; Kushawaha, Jyoti; Jahangeer, Jahangeer (Frontiers in Water, 2024)
Land use refers to how the surface of a designated area is utilized, encompassing both developed and vacant lands. The intricate interplay between population growth and the availability of natural resources gives rise to diverse challenges that are exhibited in the recharge of groundwater. This research was conducted in the Koraiyar Watershed, Coimbatore District, Tamil Nadu, India. The change in the land use land cover (LULC) was detected by digitizing the linear imaging self scanning sensor (LISS) III and LISS IV satellite images for the years 2000 and 2011 using the maximum likelihood classification algorithm. LANDSAT-8 OLI data were processed for the year 2020. The study area has subsequently undergone an assessment of groundwater levels to determine the impact between groundwater and land use land cover. The result of the study indicates a continuous decrease in the wet crop area, which is the effect of the gradual depletion of groundwater resources. Along with this, the narrowing of the water bodies and increased areas of dry crops, industrial areas, and quarries are also responsible for lowering groundwater table depletion and contamination. Settlements increased from 39 to 49 km2 from 2000 to 2011 and then gradually increased by 50 km2 in 2020 to meet the demand of the population. From 2000 to 2019, the groundwater level has been declining with respect to the LULC pattern. The increase in concrete platforms in the study can affect the infiltration. Thus, the study can aid in developing water management strategies and decisions for governmental and non-governmental policymakers.